Análisis de la oferta hotelera para los turistas en la ciudad de Iquitos, periodo 2023 - Quispe Mozombite, Jennifer Janet (2025)
His study analyzes the hotel supply for foreign tourists in the city of Iquitos during the 2023 period. Using a descriptive approach and a non-experimental, cross-sectional design, data were collected from 42 hotels categorized by the Ministry of Foreign Trade and Tourism (MINCETUR). The main objectives were to identify the number of hotels by category, assess price levels by room type, and analyze the availability of rooms and beds. The results revealed that 60% of hotels belong to the three-star category, followed by 31% in the two-star category. Regarding prices, suites represented the highest level with an average of S/ 215 per night, while single rooms averaged S/ 80. Additionally, three-star hotels concentrate most rooms (61%) and beds (70%). This analysis contributes to understanding the hotel sector in Iquitos, providing valuable information for tourism management and the development of strategies to strengthen the industry.